SFFT with a Triangle?

Geometry Level 2

Triangle A B C ABC exists such that the length of side B C BC is the average of the length of the other two sides, and cos C = A B A C \cos C=\frac{AB}{AC} . The lengths of the sides of the triangle are coprime integers. If the area of the triangle is X Y X\sqrt{Y} for positive integers X X and Y Y with Y Y being squarefree, find X + Y . X+Y.


The answer is 12.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Sanjoy Kundu
Nov 1, 2019

The key to solving this problem is to find c o s ( C ) cos(C) , as once this is done, we will have enough information to determine all three side-lengths of this problem and swiftly use Heron's Formula to finish it off. Start by neatly drawing a triangle and label the points A, B, and C, as per the problem. Since we know that that c o s ( C ) = A B / A C cos(C) = AB/AC , using the Law of Cosines is clearly the best approach. Let A B = c AB = c and A C = b AC = b . We then have c 2 = a 2 + b 2 2 a b c o s ( C ) c^2 = a^2 + b^2 - 2abcos(C) . Furthermore, we know that a = ( b + c ) / 2 a = (b+c)/2 from the problem. Substituting everything in, we are now ready to do some tedious (but extremely useful) algebra. So c 2 = ( ( b + c ) / 2 ) 2 + b 2 2 ( b ) ( ( b + c ) / 2 ) c o s ( c ) c^2 = ((b+c)/2)^2 + b^2 - 2(b)((b+c)/2)cos(c) . Carefully rearranging everything into one side and substituting c o s ( C ) = A B / A C = c / b cos(C) = AB/AC = c/b gives us a multivariable quadratic polynomial equation, namely 7 c 2 5 b 2 + 2 b c = 0 7c^2 - 5b^2 + 2bc = 0 . Now we can clearly see by inspection that c = b c=-b is a root of this quadratic, so utilizing Simon's Favorite Factoring Trick (SFFT), we can factor this multivariable polynomial as 7 ( b + c ) ( c ( 5 b / 7 ) ) = 0 7(b+c)(c-(5b/7)) = 0 . Hence we have c = b c=-b and c = 5 b / 7 c=5b/7 . However, if we plug in the former solution, we get c o s ( C ) = 1 cos(C) = -1 which implies the triangle is degenerate (and in fact a line). Hence we eliminate this extraneous solution and conclude that c = 5 b / 7 c=5b/7 , thus c o s ( C ) = 5 / 7 cos(C) = 5/7 . Now, we know that c = 5 c = 5 and b = 7 b = 7 . Since a a is defined to be the average of b b and c c , we have a = ( 5 + 7 ) / 2 = 6 a = (5+7)/2 = 6 . Finally, the semi-perimeter s s of this triangle is ( 6 + 7 + 5 ) / 2 = 9 (6+7+5)/2 = 9 , so plugging into Heron's Formula, denoted by ( s ) ( s a ) ( s b ) ( s c ) \sqrt{(s)(s-a)(s-b)(s-c)} , gives us ( 9 ) ( 9 6 ) ( 9 7 ) ( 9 5 ) \sqrt{(9)(9-6)(9-7)(9-5)} which simplifies to ( 9 ) ( 3 ) ( 2 ) ( 4 ) \sqrt{(9)(3)(2)(4)} which simplifies to 216 \sqrt{216} which finally simplifies to 6 6 6\sqrt{6} . Thus, X = 6 X = 6 and Y = 6 Y = 6 , and 6 + 6 = 12 6 + 6 = 12 , as desired.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...